Decision Support System of Achieving Employees Using SWOT Method at PT. Dana Darma Pratama (DDP) Muko-muko - Windy Oktaviani; Ujang Juhardi (Jurnal Komputer, Informasi dan Teknologi (JKOMITEK), 2022)
Decision making constitutes the selection of several alternative actions that exist to achieve one or more goals that have been implemented. By using a SWOT analysis is a tool to determine the position. This study aimed to build a data processing application in the promotion system for permanent employees. To achieve a bachelor's degree at the Faculty of Informatics, University of Muhammadiyah Bengkulu. Testing testing method is testing that is carried out to ensure the application runs according to the desired objective. The data collection process carried out by the author is observation, interviews and literature study.